2016
DOI: 10.1088/1361-6560/62/1/202
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose lung cancer screening with photon-counting CT: a feasibility study

Abstract: Objective To evaluate the feasibility of using a whole-body photon-counting detector (PCD) CT scanner for low dose lung cancer screening compared to a conventional energy integrating detector (EID) system. Materials and Methods Radiation dose-matched EID and PCD scans of the COPDGene 2 phantom were acquired at different radiation dose levels (CTDIvol: 3.0, 1.5, and 0.75 mGy) and different tube voltages (120, 100, and 80 kVp). EID and PCD images were compared for quantitative Hounsfield unit accuracy, noise l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 28 publications
2
71
1
Order By: Relevance
“…The suppression of electronic noise with PCD CT leads to better attenuation stability and lower image noise; this concept has been extensively evaluated in a specialized lung phantom for chest CT (9,10). PCD CT demonstrated up to 11.8% less image noise and 11.4% higher CNR in low-contrast lesion detectability (eg, ground-glass nodules and emphysema) for multiple combinations of tube current and tube voltage settings.…”
Section: Study Populationmentioning
confidence: 99%
“…The suppression of electronic noise with PCD CT leads to better attenuation stability and lower image noise; this concept has been extensively evaluated in a specialized lung phantom for chest CT (9,10). PCD CT demonstrated up to 11.8% less image noise and 11.4% higher CNR in low-contrast lesion detectability (eg, ground-glass nodules and emphysema) for multiple combinations of tube current and tube voltage settings.…”
Section: Study Populationmentioning
confidence: 99%
“…18 Therefore, we matched the tube voltage and tube current-time product values to obtain a similar energy spectrum and the number of x-ray photons incident on both detector systems, allowing a fair comparison. 13 The effective dose was calculated by multiplying the dose-length product by 0.0021 mSv/mGy as the constant k-value for brain imaging.…”
Section: Ct Scan Protocolmentioning
confidence: 99%
“…8 In addition, the direct conversion and counting of individual photons provide a better estimate of the underlying photon statistics, which, in turn, may improve image quality by reducing image noise. 8,[12][13][14] We hypothesized that the combined effects of better contrast and reduced noise may lead to better overall GM-WM differentiation in brain PCD CT.…”
mentioning
confidence: 99%
“…Previous studies using this scanner demonstrated that the PCCT was capable of providing clinical image quality at X-ray photon flux encountered in routine CT exams, which were commensurate with commercial EID systems (Yu et al, 2016a, Pourmorteza et al, 2016). Benefits of this specific PCCT scanner over the state-of-the-art CT scanner using EIDs have been previously demonstrated and include improved CNR, increased spatial resolution, and better HU stability at low dose (Gutjahr et al, 2016, Leng et al, 2017, Symons et al, 2016). These studies, however, focused only on traditional image quality in a single-energy mode, i.e.…”
Section: Introductionmentioning
confidence: 99%